On Gastronomic Jurisprudence and Judicial Wellness as a Matter of Competence - Alan C. Logan; Colleen M. Berryessa; Pragya Mishra; Susan L. Prescott (Laws)
For over a century, critics have postulated that a judge’s state of hunger or post-prandial mental state is a determinant of judicial outcomes. This idea, known in contemporary discourse as the ‘judicial breakfast,’ is used as a surrogate of the larger ways in which biases, even if the individual is not aware of them, influence judicial outcomes. In 2011, the publication of a landmark study paired parole decisions with judicial meal breaks, inviting a literal interpretation of the judicial breakfast. Since that publication, the literature on nutritional neuropsychology has grown rapidly. The findings of these studies are highly relevant to judges experiencing high stress levels, including workload demands and activities within the adversarial system. This stress represents significant harm to an individual judge’s wellbeing, and based on updated findings within neuropsychology, has potential relevance to judicial outcomes. Emergent research indicates that dietary choices and blood/brain glucose have the potential to act as important mediators of decision-making under conditions of stress and fatigue. With proper evidence-based attention, we can better understand the extent to which diet and lifestyle can positively influence judicial wellness and, by extension, support or refute the longstanding assumptions surrounding the “hungry judge effect” and gastronomic jurisprudence.